Sekélyvizű tavak jellegzetességei és problémái - Kutics, Károly (Acta Scientiarum Socialium, 2013)
Peculiarities and Problems of Shallow Lakes Shallow lakes are more vulnerable to human activities and natural changes than deep ones. Shallowness can be measured through the dynamic ratio of a lake and lakes of similar shallowness can be compared in terms of sensitivity and vulnerability to various stresses. Several shallow lakes and communities in their basins experience disastrous changes due to mistakes committed in lake and watershed management as well as due to climate change. 11 shallow lakes with a certain degree of similarity to Lake Balaton were selected for analysis from Europe, North-America and Japan. It has been found that Lake Balaton does not show extreme characteristics as compared to the other lakes. Eutrophication is a common problem of all lakes, though the level of seriousness varies from very serious to acceptable. Most lakes have water level problems due to water overuse or climate change. Dropping water level and shrinking of surface area always result in deterioration of water quality and loss of aqueous habitat. Some lakes apply water conveyance from other watershed to improve water balance and manage level drop and/or large fluctuation. Water quality improvement measures applied include stopping or restriction of agricultural activities, sewage treatment, dredging, biomanipulation, wetland restoration with filtration functions, direct runoff control, soil treatment to immobilize phosphorus and pesticides, etc. Magnitude of measures (spending) is neither proportional to the seriousness of the problem nor to the population affected but it is more a function of the economic power of the countries. Most lakes and watersheds have a management plan developed but these plans do not entirely reflect the total economic value (TEV) of the lakes. A detailed analysis and development of the methodology of TEV estimation could be an important contribution to this research project.
Keywords: shallow lakes; eutrophication, water level; common problems; measures